Guided inquiry with sparkol videosribe in science learning: a study of students' scientific attitudes - Abdur Rasyid; Mukarramah Mustari; Yunia Nabila Aziziy; Dede Salim Nahdi (International Journal of Educational Innovation and Research, 2022)
Scientific attitude is an important element in learning Natural Sciences (IPA) which must be instilled early on. However, many studies reveal that students in elementary schools still have a low scientific attitude so it takes some effort to improve it. Efforts that can be done include implementing a learning model and media that are thought to facilitate students in developing their scientific attitude, one of which is the Guided Inquiry model with Sparkol Videoscribe learning media. This research has the aim of improving students' scientific attitudes by applying the Guided Inquiry model assisted by Sparkol Videoscribe in science learning. The method used in this study is a quasi-experimental type of experimental research and the Nonequivalent control group design. The population in this study were all grade 5 students of elementary schools in Cigasong Sub-district, Majalengka with the sample being grade 5 students of SDN Cicenang 1, Majalengka of two classes. The results of the study illustrate that the scientific attitude of students who obtained the Guided Inquiry model assisted by Sparkol Videoscribe was better than students who obtained conventional learning. From these results, it can be concluded that the Guided Inquiry model assisted by Sparkol Videoscribe is effective in improving students' scientific attitudes.